Microscopic Analysis of the Mechanical Stability of an SEI Layer Structure Depending on the FEC Additive Concentration in Na-Ion Batteries: Maximum Appearance in Vickers Hardness at Lower FEC Concentrations - Bouibes, Amine; Sakaki, Nisrine; Nagaoka, Masataka (ACS omega, 2023)
The stability of the solid electrolyte interphase (SEI) layer during the charging–discharging cycles is reasonably related to its microscopic elasticity. For the first time, it was theoretically revealed that each component of the elastic moduli takes a maximum at an optimal concentration of 1.0 vol % of fluoroethylene carbonate (FEC) for the SEI layer formed in the FEC-added NaPF6/PC-based electrolyte. The elastic constants indicated that the SEI layer formed at lower FEC concentrations is more resistant to tensile and shear deformations. The optimal hardness is sensitive in the lower FEC concentrations although it simply decreases as the FEC concentration increases. This is due to the formation of a denser SEI structure with small cavities in the lower concentrations. The results are excellently consistent with the experimental one, justifying the microscopic understanding of the FEC additive effect on the mechanical stability of the SEI layers designed through the Red Moon simulation.